KUALITAS BAKTERIOLOGI RUJAK CINGUR DITINJAU DARI HIGIENE PERORANGAN PENJUAL RUJAK CINGUR” - Umi Rahayu; suparlan . (JURNAL PENELITIAN KESEHATAN, 2014)
Destination this study was to determine the microbiological quality of the salad plate cingur based rate Total (ALT), and Escherichia coli content in terms of personal hygiene seller cingur salad. The research method was a descriptive study with cross sectional approach.The results showed action individual sellers higene salad cingur 83.33% eligible, 16.67% are not eligible. Results of bacteriological quality checks on the first sample inspection, based on the results of Total Plate Count meets the requirements. Based on the examination of E. coli 66.66% eligible, 33.33% noteEligible. On examination of the sample to replicate the results ALT qualify, E.coli 83.33% eligible, 16.67%  not eligible. It is suggested to the seller salad cingur to improve personal hygiene measures, measures to improve hygiene and sanitation equipment point of sale environment. To the health center to conduct training Kalirungkut advised to conduct counseling or training on Health Food Drinks specifically for the seller and the salad cingur Surabya City Health Department in order to make the program checks the quality of bacteriology (E. coli) cingur salad meals on a regular basis with no cost / free. Keywords: ALT, E. coli, Personal hygiene.